2018
DOI: 10.1002/ajpa.23752
|View full text |Cite
|
Sign up to set email alerts
|

Buffered or impaired: Maternal anemia, inflammation and breast milk macronutrients in northern Kenya

Abstract: Background: Maternal anemia has adverse consequences for the mother-infant dyad. To evaluate whether and how milk nutrient content may change in ways that could "buffer" infants against the conditions underlying maternal anemia, this study assessed associations between milk macronutrients and maternal iron-deficiency anemia (IDA), non-iron-deficiency anemia (NIDA), and inflammation.Methods: A secondary analysis of cross-sectional data and milk from northern Kenya was conducted (n = 204). The combination of hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…Data collection took place during a prolonged drought and food shortage; many mothers were coping with the food shortage by reducing food variety, meal size or the number of meals for their consumption (Apland & Fujita, , , ; Apland, Fujita, & Chang, ; Fujita, ; Fujita, Apland, & Chang, ), and prioritizing their children in allocating limited amount of foods within households (Fujita, ). Our subsequent research found that low BMI (Fujita, ; Fujita, Brindle, Lo, Castro, & Cameroamortegui, ), vitamin A deficiency (Fujita, ; Fujita et al, ; Fujita, Lo, & Brindle, ), and iron deficiency (Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita & Wander, ) were prevalent among these mothers.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Data collection took place during a prolonged drought and food shortage; many mothers were coping with the food shortage by reducing food variety, meal size or the number of meals for their consumption (Apland & Fujita, , , ; Apland, Fujita, & Chang, ; Fujita, ; Fujita, Apland, & Chang, ), and prioritizing their children in allocating limited amount of foods within households (Fujita, ). Our subsequent research found that low BMI (Fujita, ; Fujita, Brindle, Lo, Castro, & Cameroamortegui, ), vitamin A deficiency (Fujita, ; Fujita et al, ; Fujita, Lo, & Brindle, ), and iron deficiency (Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita & Wander, ) were prevalent among these mothers.…”
Section: Methodsmentioning
confidence: 92%
“…Future research should replicate this study and further examine the impacts of other maternal characteristics on breast milk as another avenue of how maternal health may impact milk and, ultimately, infant well-being. Our team is currently investigating the effects of maternal micronutrient deficiencies, inflammation/infection, and anemia on milk in a separate study (Fujita et al, 2018a(Fujita et al, , 2018b. A limitation of this study was that the milk specimens had been subjected to prolonged cryogenic storage at −80 C and underwent freeze/thaw cycles prior to being assayed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, prospective cohort data with maternal Hb values at multiple time periods across the continuum of preconception, pregnancy, and postpartum would allow us to better assess the role of the timing and guide potential trimester‐specific cutoff decisions. While it was beyond the scope of the current review, the association between postpartum maternal Hb and maternal and child health outcomes may also merit further examination, including a possible relationship between maternal anemia during lactation and breastmilk macronutrient composition . Furthermore, the majority of the literature that examines the role of the timing on health outcomes has focused on low Hb.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding mothers can also be negatively affected by IDA, considering that maternal nutritional status is closely associated with the quality of human milk; therefore, impairment in human milk content may occur due to maternal anemia. Maternal anemia can alter the quality of human milk both in the nutrient and non-nutrient content [14].…”
Section: Introductionmentioning
confidence: 99%